Morphological changes in liver cells of hypercholesterolaemic-induced rats and hepG2 cell lines associated with edible bird’s nest supplementation - Mohd Noor, Mohd Akmal (2020)
Edible bird’s nest (EBN) is an animal-based natural product that has high interest in Chinese committee. Since in the Tang Dynasty (618-907 CE), it had been consumed frequently by the royal families for well-being purposes. This polymerized swiftlet’s salivary secretion is mainly composed of protein that presence in the form of glycoprotein. It has been anecdotally claimed to have broad medicinal benefits, including metabolic stimulant. Nonetheless, the effect of EBN supplementation on the cholesterol metabolism with scientific evidence is poorly elucidated. Therefore, we hypothesised the EBN supplementation is able to improve cholesterol metabolism in HepG2 cell lines and hypercholesterolaemic-induced rats. This study focuses on evaluating the effect of EBN supplementation on the cholesterol metabolism via assessing the relevant genes expression, quantifying hepatic cholesterol concentration, measuring blood lipid profiling, localizing important structure and receptor in cholesterol metabolism, and assessing hepatic and extra-hepatic microscopic changes in the HepG2 and hypercholesterolaemic-induced rats. Cellular toxicity assessment of the edible bird’s nest extract (EBNE) at different concentrations (0.2, 0.5, 0.8, 1.0 and 1.5 mg/mL) was done and revealed the cell viability remains as high as 71% even at the highest concentration (1.5 mg/mL) after 24 hours incubation. Thus, in the subsequent assay the Hep-G2 was supplemented with EBNE at three different concentrations (0.5, 1.0 and 1.5 mg/mL) in high lipid media [exogenous lipid (1:500) and cholesterol (1:250)] for 24 hours. Besides that, there were three control groups including baseline control (BC) that cultured in AMEM media only, negative control (NC) in high lipid media, and positive control (PC) in high lipid media with Simvastatin (4.60 μg/mL) as an anti-cholesterol drug. Quantification of gene expression for both low-density lipoprotein receptor (LDLR) and acyl Coenzyme A: cholesterol acyltransferase 2 (ACAT2) were significantly up regulated in a dose-dependent manner. However, 3-hydroxyl-3-metylglutaryl coenzyme A reductase (HMGCR) was observed significantly to down-regulate this enzyme at the highest dose of EBNE (1.5 mg/mL). Quantitatively, distribution of immunofluorescence intensity against LDLR protein and lipid droplets (LDs) was increased as the EBNE concentration increased. Total cholesterol storage was showing the amount of cholesterol stored in the LDs increased as the concentration of EBNE increased. In the 12 weeks in-vivo study, a total of 30 male Sprague Dawley rats aged 10-week old were randomly assigned into five different groups (n=6); BC (normal rat diet), NC [hypercholesterolaemia induced with high-fat diet (HFD) and Triton-X 100 (150 mg/kg SQ q42d)], PC (hypercholesterolaemia with Simvastatin 10 mg/kg PO SID), EBNE [hypercholesterolaemia with EBNE (6.5 mg/kg PO SID)] and EBNS [hypercholesterolaemia with EBNS (843.2 mg/kg PO SID)]. Post-treatment blood lipid profiling was showing the EBNS group significantly reduced the triglycerides (TAG), total cholesterol (TC), low-density lipoprotein (LDL) and very low-density lipoprotein (VLDL), compared to the NC group and but only TAG and LDL significantly reduced up to BC group. Meanwhile, the EBNE group showed significant reduction for TC and LDL only compared to NC but not reduced up to the BC group. Statistically, both EBNS and EBNE group were showing significant elevation of high-density lipoprotein (HDL) compared to the NC and BC group but not as high as in the PC group. Nonetheless, the HDL of EBNS group had two-fold significant increment compared to EBNE group. Remarkably, cardiogenic indices that predicting cardiac diseases and atherosclerosis occurrence showed a significant protective effect in the EBNS group only, which comparable with PC’s indices. The hepatic cholesterol concentrations in the EBNS and EBNE were significantly reduced as compared to the NC. Gene expression revealed EBNS significantly down-regulated HMGCR and proprotein convertase subtilisin/kexin 9 (PCSK9) which stimulating and maintaining the upregulation of LDLR via cleavage of sterol regulatory element-binding protein 2 (SREBP2). Concomitantly, EBNS up-regulated also the cytochrome P450 family 7 subfamily A member 1 (CYP7a1) for bile production. On the other hand, EBNE was observed to up-regulate the expression of LDLR via cleavage of SREBP2 only. Grossly, liver of rat fed on EBNS appeared mild yellowish discolouration, meanwhile the EBNE group was observed moderate yellowish discolouration. Histological examination of the liver revealed mild hepatic steatosis in the EBNS group and mild non-alcoholic steatohepatitis (NASH) in EBNE group. This finding was consistent with the ultrastructure finding (TEM), whereby the mitochondria of EBNS were demonstrated enlarged with intact mitochondrial membrane, meanwhile the mitochondria in the EBNE group showed swollen with loss of cristae and translucent matrix indicating liver injury. The hepatic tissue sections were also immunologically-labelled with fluorescence against the LDLR and demonstrated high intensity expression of LDLR in the EBNS (5.65 ± 0.12), which statistically equivalent to the PC (5.53 ± 0.17) group. Meanwhile, EBNE (3.54 ± 0.04) group appeared lower LDLR distribution compared to EBNS group, but ameliorated than NC (1.81 ± 0.06). Quantitative SEM revealed the cranial thoracic aorta of NC and EBNE were significantly occluded the aortic lumen up to 31% and 30%, respectively; compared to the BC (0%). Meanwhile, EBNS documented insignificant aortic lumen occlusion (<1%). These outcomes were consistent with degree of immunoreactivity in the CD40 immunoperoxidase assay, in which detecting atherosclerosis biomarker. Renal tissue demonstrated absence of glomerulonephritis in the EBNS group, but prominently observed in the EBNE with thickening of the glomerular basement membrane. These findings were in line with detection of the renal inflammasome (NLRP3) in the tubules of EBNE group which covered up to 61% of the tissue section, compared to the EBNS which less than 17% immunoreactivity. Concurrently, inflammatory cells in the renal interstitial space was showing mild and moderate infiltration in respective group. As a conclusion, EBNE shows significant cholesterol improvement in the in-vitro study not in the in-vivo model. Nonetheless, in the hypercholesterolaemic-induced rats, EBNS was profoundly exhibited a significant effect in improving cholesterol metabolism and slowing progression of non-alcoholic fatty liver disease (NAFLD), atherosclerosis and chronic kidney disease (CKD).